2022
DOI: 10.3389/fenvs.2022.896702
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dryland Trees With Remote Sensing. Part A: Beyond CORONA—Historical HEXAGON Satellite Imagery as a New Data Source for Mapping Open-Canopy Woodlands on the Tree Level

Abstract: Monitoring woody cover by remote sensing is considered a key methodology towards sustainable management of trees in dryland forests. However, while modern very high resolution satellite (VHRS) sensors allow woodland mapping at the individual tree level, the historical perspective is often hindered by lack of appropriate image data. In this first study employing the newly accessible historical HEXAGON KH-9 stereo-panoramic camera images for environmental research, we propose their use for mapping trees in open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In Part A of our study (Marzolff et al, 2022) we found that HEXAGON imagery has a remarkably similar potential for identifying individual trees compared to the WorldView images, although both have limited ability for mapping small trees and trees in clumped-canopy groups. By using the combination of tree locations known a priori from field mapping with a retrospective mapping approach opting for stability in case of doubt, we could ensure very high accuracy for tree-density and tree-cover measures in 2018 and a conservative tendency towards underestimation rather than overestimation of change.…”
Section: Satellite-based Tree-cover Change Mappingmentioning
confidence: 74%
See 4 more Smart Citations
“…In Part A of our study (Marzolff et al, 2022) we found that HEXAGON imagery has a remarkably similar potential for identifying individual trees compared to the WorldView images, although both have limited ability for mapping small trees and trees in clumped-canopy groups. By using the combination of tree locations known a priori from field mapping with a retrospective mapping approach opting for stability in case of doubt, we could ensure very high accuracy for tree-density and tree-cover measures in 2018 and a conservative tendency towards underestimation rather than overestimation of change.…”
Section: Satellite-based Tree-cover Change Mappingmentioning
confidence: 74%
“…As a representative example for the tree-cover change maps 1972-2018, Figure 4 shows the test site MAO1n, where the overall tree density and cover change is quite similar to the average of all 30 test sites (compare with change map Figure 7 in Marzolff et al, 2022). The tree density at MAO1n remained unchanged at 55 trees ha −1 , and 33 (or 60%) of the 1972 trees remained in the same size class (yellow circles).…”
Section: Changes Of Tree Cover and Density 1972-2018mentioning
confidence: 95%
See 3 more Smart Citations